Tetrapod Fracture: Surgical Anatomy Revisited As A Guide For 3D Reduction Using Carroll Girard T-Bar Screw - Kreshanti, Prasetyanugraheni; Gianni, Livia Faranita (Lingkar Studi Bedah Plastik Foundation, 2017)
Background: Zygomaticomaxillary complex plays a key role in the structure, function, and aesthetic appearance of the facial skeleton. Using Carroll Girard T-bar screw allows easy manipulation of the zygomaticomaxillary complex fracture. The goal of the treatment is three dimensional (3-D) restoration of the disturbed anatomy. Methods: After exposing the fracture sites using technique such as lower eyelid, Dingman (lateral brow) or maxillary vestibular approach, the Carroll Girard T-bar screw is then attached to the lateral aspect of the malar eminence to freely move the zygoma according to the x,y, and z axis. Zygomaticosphenoid suture acts as the anatomical landmark for adequate reduction. Conclusion: Open reduction and internal fixation is the principle of management in displaced ZMC fractures, aided by the use of Carroll Girard T-bar screw which allows easy manipulation and rotation for the zygomatic bone using the reference axis x, y and z.